An Examination of Lactobacillus paracasei GKS6 and Bifidobacterium lactis GKK2 Isolated from Infant Feces in an Aged Mouse Model. (9th April 2021) - Lin, Shih-Wei; Tsai, You-Shan; Chen, Yen-Lien; Wang, Ming-Fu; Chen, Chin-Chu; Lin, Wen-Hsin; Fang, Tony J.
Abstract : Supplementary which could maintain normal physiological mechanisms and functions while aging has drawn our attention due to the population aging in recent years. Probiotics have been believed with desirable properties such as antioxidation and anti-inflammatory for delaying the aging process. However, the age-related experiments conducted in the mammalian models with probiotics were few. In this study, we demonstrated the effects of administration of probiotics Lactobacillus paracasei GKS6 (GKS6) and Bifidobacterium lactis GKK2 (GKK2), respectively, at the dosage of 5.0 × 10 9 cfu/kg BW/day for fourteen weeks in senescence-accelerated mouse prone 8 (SAMP8) mice. The three-month-old SAMP8 mice were divided into three groups: control, mice fed with GKS6, and mice fed with GKK2. There were ten females and ten males in each group. The SAMP8 mice fed with probiotics GKS6 and GKK2 showed a significantly lower degree of aging followed by Takeda's grading method on the eleventh week of the experiment. The GKK2 group showed significantly increased forelimb grip strength in male SAMP8 mice and muscle fiber number in both genders. Compared to the control, both GKS6 and GKK2 presented a significant increase in liver superoxide dismutase and catalase activities. In addition, a significant decrease in the levels of liver thiobarbituric acid-reactive substances was observed in the probiotics group. These results suggested that probiotics GKS6 and GKK2 could act as antioxidants in delaying the process of aging and preventing age-related muscle loss.